Toxoplasma chorioretinitis in primary myeloperoxidase MPO deficiency: A case report - D.V. Maltsev; O.O. Hurzhii (Ukrainian Society of Ophthalmologists, 2019)
We present a clinical case of primary partial myeloperoxidase (MPO) deficiency in a young female patient with recurrent episodes of opportunistic infections. Initially, she presented to the clinical immunologist (DVM) seeking help with her severe clinical manifestations of chronic fatigue syndrome. Blood polymerase chain reaction (PCR) was positive for Epstein Barr virus. Brain MRI showed signs of external hydrocephalus and bilateral hippocampal sclerosis. After double antiviral therapy with valacyclovir (3 g daily, orally) and recombinant human alpha-2b-interferon (3 mln units every other day intramuscularly) for 3 months, the blood PCR became negative, and clinical symptoms completely resolved. A year later, the patient presented again to the immunologist, but this time due to abruptly decreased vision in her right eye. She was referred to the ophthalmologist. There were ophthalmoscopic and fluorescein angiography (FA) signs of acute chorioretinitis in the right eye. Serological testing revealed increased IgM titers to Toxoplasma gondii. Blood PCR was positive for Toxoplasma gondii. The patient was diagnosed with acute Toxoplasma chorioretinitis based on the clinical-and-laboratory, ophthalmoscopic and FA findings, and was treated for toxoplasmosis with spiramycin (1.5 mln units diluted in 200 ml of 0.9% normal saline, daily for 14 days, intravenously, and thereafter, 1000 mg three times a day after meals, for 14 days, orally). In addition, she received continuous basic immunomodulating therapy with recombinant human interferon gamma (500,000 units every other day at bedtime for 6 months) for compensation of MPO deficiency, as per the national guidelines. This normalized the percentage content and functional activity of MPO in neutrophils, and enabled prevention of further opportunistic infection episodes. This case report demonstrates that treatment of eyes affected by opportunistic infections in immunocompromised patients requires cooperation between ophthalmologists and clinical immunologists.